2010
DOI: 10.1530/eje-10-0508
|View full text |Cite
|
Sign up to set email alerts
|

Altered fasting and postprandial plasma ghrelin levels in patients with liver failure are normalized after liver transplantation

Abstract: Context: Anorexia is a problem of paramount importance in patients with advanced liver failure. Ghrelin has important actions on feeding and weight homeostasis. Experimental data exist, which suggest that ghrelin could protect hepatic tissue. Both fasting and post-oral glucose tolerance test (OGTT) ghrelin concentrations are controversial in liver cirrhosis and are unknown after liver transplantation. Objective: Our aim was to study fasting ghrelin concentrations and their response to an OGTT in liver failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
(94 reference statements)
1
7
0
Order By: Relevance
“…Other contributors that could facilitate the expansion of the somatotroph tumor cells are hypothalamic GHRH or somatostatin, paracrine growth factors, and ghrelin [1, 3]. Recent data suggest the importance of the role of ghrelin in the pathophysiological regulation of GH [46]. Over 90% of patients with acromegaly have a benign monoclonal pituitary adenoma, which are not surrounded by hyperplasic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Other contributors that could facilitate the expansion of the somatotroph tumor cells are hypothalamic GHRH or somatostatin, paracrine growth factors, and ghrelin [1, 3]. Recent data suggest the importance of the role of ghrelin in the pathophysiological regulation of GH [46]. Over 90% of patients with acromegaly have a benign monoclonal pituitary adenoma, which are not surrounded by hyperplasic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Other contributors that could facilitate the expansion of the somatotroph tumor cells are hypothalamic GHRH or somatostatin, paracrine growth factors and ghrelin [2], [4]. Recent data suggest the importance of the role of ghrelin in the pathophysiological regulation of GH [5][7]. Current treatment for acromegaly includes neurosurgery, radiotherapy and medical therapy with dopamine agonists, somatostatin analog (SSA), and the GH-receptor antagonist pegvisomant [2], [8][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies showed protective effect of ghrelin on the liver [20, 21] and decreased circulating ghrelin level in patients with NAFLD has been reported [22]. Furthermore, decreased plasma levels of ghrelin in patients with liver failure were normalized after liver transplantation [23]. Several experimental studies have demonstrated the presence of ghrelin in gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%